Et 2020 – European Education System on the Border Between Globalization, Technology and Revivement of the Identitary Creativity - Porumbescu Alexandra (European Scientific Journal, ESJ, 2017)
Education is perceived, by the developed societies, as the key element of progress and welfare, being able to empower new generations with knowledge and skills aimed to contribute to the evolution of the world we live in. Designed as a political, economic, but, above all, social project, the European Union supports its member states in their attempts to increase both the quality and the accessibility of education, by setting common goals and designing common instruments to achieve them. However, the process of modernizing the European system of education is not an easy one, nor can it be concluded in a short period of time. This is the reason why, for several decades, the European institutions have released a number of official documents meant to create the framework for an education system that would match the challenges and opportunities of the globalized world we live in. The aim of this paper is to analyze and discuss the ways in which the national management of the education system provided by the governments of the Member States is complemented by the tools provided by the common European institutions. In order to achieve this, we will highlight the main issues tackled by previous documents, along with the results of such policies, focusing on Education and training 2020 (ET 2020).